Dasatinib synergizes with ATRA to trigger granulocytic differentiation in ATRA resistant acute promyelocytic leukemia cell lines via Lyn inhibition-mediated activation of RAF-1/MEK/ERK. (September 2018) - Ding, Ming; Weng, Xiang-qin; Sheng, Yan; Wu, Jing; Liang, Cui; Cai, Xun
Abstract: All-trans retinoic acid (ATRA) resistance has been a critical problem in acute promyelocytic leukemia (APL) relapsed patients. In this study, dasatinib synergized with ATRA to trigger differentiation in ATRA-resistant APL cell lines. The combined treatment activated RAF-1, MEK and ERK as well as enhanced ATRA-promoted up-regulation of the protein level of PU.1, C/EBPβ and C/EBPε. U0126 (MEK specific inhibitor) and sorafenib tosylate (RAF-1 specific inhibitor) suppressed the combined treatment-induced differentiation, ERK phosphorylation and the up-regulation of C/EBPs and PU.1. Sorafenib tosylate also attenuated the MEK activity. However, the combined treatment did not enhance Ras activity and Ras inhibitor neither blocked MEK activation nor inhibited differentiation. Therefore, the combined treatment induced differentiation via Ras independent RAF-1/MEK/ERK. Earlier than RAF-1 activation, dasatinib suppressed Lyn activity, the predominant activated Src family kinase (SFK) and dephosphorylated RAF-1 at S259. Furthermore, SFK inhibitor, PP2 did suppress Lyn activity and mimicked the effect of dasatinib on ATRA-induced differentiation as well as decreased phosphorylation of RAF-1 at S259. Thus, it was suggested that Lyn inhibition might activate RAF-1 by the dephosphorylation of RAF at S259 and lead to differentiation. In conclusion, the combination of dasatinib and ATRA could overcome ATRA resistance through Lyn inhibition-mediated activation of RAF-1/MEK/ERK. Highlights: Dasatinib and ATRA triggered differentiation in ATRA resistant APL cell lines. The combination induced differentiation via Ras independent RAF-1/MEK/ERK. Dasatinib suppressed Lyn activity, the predominant activated SFK in both cell lines. RAF-1 was activated by Lyn inhibition-mediated dephosphorylation of S259.